Odpowiedzi

2009-10-03T23:03:46+02:00
Pierwiastek z dwóch * ( trzy pierwiastek z osmiu - dwa pierwistki z trzydziestudwoch) =

√2 * (3√8 - 2√32) = 3*√8*√2 - 2*√32*√2 = 3√16 - 2√64 = 12-16 = -4
2009-10-03T23:04:47+02:00
Pierwiastek z dwóch * ( trzy pierwiastek z osmiu - dwa pierwistki z trzydziestudwoch) =
√2*(3√8-2√32)=3√16-2√64=3*4-2*8=12-16=-4
  • Użytkownik Zadane
2009-10-03T23:07:32+02:00
Rozkładasz √8=√(4×2)=√4x√2=2√2 i podobnie √32=√(4x4x2)=√4x√4x√2=2x2x√2=4√2, wtedy masz, że √2x(3√8-2√32)=√2x(3x2√2-2x4√2)=√2x(6√2-8√2)=√2x(-2√2)
=-2√4=-2x2=-4